The Effects of Moisture Content Variation on Some Engineering Properties of Almond Seed (Terminalia Catappa) - Atteh, Bamidele; Olukemi, Oguntoyinbo; Bosede Adelola, Orhevba (Department of Technology of Agricultural product (THP) Jambi University, 2021)
The physical and mechanical properties of Almond seed at different moisture content levels of 6.78%, 12.39%, 17.11% and 21.97% were investigated in this study. The physical properties include geometric mean diameter, bulk density and angle of repose; they were determined using standard procedures. The length, width and thickness obtained for the 100 samples of the almond seeds were in the range of 25.42-28.63mm, 23.69-26.63mm, and 7.51-9.18mm respectively. The result shows a high uniformity on the seed sizes and significant variations between the length, width and thickness. The calculated values of the geometric mean diameter and sphericity ranged from 16.48-19.07mm and 64.66- 66.63% respectively. The results of the surface area varied from 853.6-1143.04mm2. The result also indicated a high variation in the surface area of the seeds with respect to the different moisture content levels. The mechanical properties which include rupture force, compressive strength and tensile strength were determined on the seeds. The mechanical properties show that the fracture force and compressive strength decreased from 2689N to 2499N, 410N/mm2 to 398 N/mm2respectivelywith an increase in moisture content (6.78%-21.9%). The tensile strength obtained for moisture levels of 6.78%, 12.39%, 16.11% and 21.9% were 3.20Mpa, 3.90Mpa, 4.20Mpa and 4.60Mpa respectively